Saberes de professores sobre a práxis pedagógica de Matemática nos anos iniciais - Oliveira, Gracielle Aparecida Mendonça de (2020)
This qualitative research was carried out with the participation of a group of fifteen teachers who teach Mathematics, from the 2nd to the 5th year of elementary school, in a public school in the city of Uberlândia - Minas Gerais. The actions and reflections of this study were conducted by the following problematic question: How do the knowledge of teachers who teach mathematics contribute (or not) to the performance of their students? Seeking to answer this question, we had as main objective to investigate, identify and analyze the knowledge of teachers who teach Mathematics, their relationship with the pedagogical praxis and how they contribute (and if they contribute) with the academic performance of their students. Due to the impossibility of covering the largest number of possible schools located in the city of Uberlândia, we analyzed the result of IDEB in 201, we identified the schools that obtained the highest grades in this index and chose to investigate one of them. The analysis material consisted of interviews and a reflective session. The aspects observed and the materials produced were of great value in the construction and understanding of the relationship between teaching knowledge and their respective pedagogical praxis, in the contribution of students' school performance. Data analysis was carried out listing two categories: Understanding the teaching of mathematics and pedagogical praxis in the teaching of mathematics. By the analysis carried out, it we can obtain as results the understanding that the knowledge of teachers who teach mathematics through the organization of teaching in this subject, the development of pedagogical praxis endowed with intentionalities and the performance of activities in groups of students can contribute to the appropriation of mathematical knowledge by those involved in the mathematics teaching process, imbued with reflections and mediating actions that significantly contribute to students' academic performance. Therefore, it is clear, that the social relationships developed by teachers are of paramount importance in the development of mathematics teaching, because when they are organized from a pedagogical práxis with intentions, motivated by what the teacher accomplishes and proposes to his students, contributes significantly to the mathematics teaching process and consequently to students' scholl performance.